Paisagem e cultura : transformações na pequena propriedade rural norte paranaense entre 1950 e 1980 - Santos, Liriani de Lima (2019)
The research developed in this thesis shows the transformations printed in the spatial organization and in the social relations of the small rural property in the context of the process of modernization of agriculture, assured by the economic and agricultural policies of the country. The reading provided by the Cultural and Agrarian Geography permeates the work, whose methodology privileges the field work. The emergence of small rural properties in the north of Paraná is linked to the occupation and official settlement of the state that only gained momentum with the directed colonization led by real estate companies. Among these companies, the North Paraná Land Company (Companhia de Terras Norte do Paraná) was highlighted, which, after being nationalized, changed its name to Northern Paraná Land Improvement Company (Companhia Melhoramentos Norte do Paraná). At the height of its activity in the state the company created municipalities, divided urban and rural lots and invested in a transport structure that attracted buyers. The parceling of rural plots in small farms was a sales and profit strategy, since the company knew its clientele, mostly ex-settlers, foreigners or descendants, from coffee farms in São Paulo, little capitalized and attracted by the possibility of land ownership and gains from growing coffee. During the period that the coffee economy was dominant in the whole state, an infrastructure dedicated to the coffee production process was erected, the spatial organization of the small rural properties was also planned with coffee as the protagonist. With the process of modernization of agriculture, the framework that supported the cultivation of coffee was replaced. The intensity and speed of the modernization process, although it has not reached the North of the state in a homogeneous way, being more vehement in the areas more propitious to mechanization, due to the pedological and relief conditions, brought economic, social and cultural consequences. It was not only the spatial organization of small properties that has been altered, a whole way of life came to be transformed. In this period, agricultural policies that mostly have always been directed towards large property, have contributed to land concentration, but not to the end of small properties, that resist adjusting to some policy that allows them to survive, or adjusting to the market and the commercialization imposed by the large property that produces on a large scale; or by inserting itself into economies geared specifically to small property. Used as a strategy for the colonizing occupation of the privately owned companies that acted in the state, this economy and way of life almost disappeared when another economic policy directed to agriculture was imposed, now turned to the large-scale production carried out by the large properties. There are, admittedly, a much smaller number of small properties in the areas in which agricultural modernization has been implemented, but we also recognize that they continue to be part of the agricultural economy, recreating an economy that allows its development and maintaining, appropriate to current life (2019), a way of life linked to the land and the external realities, as the nearest city and the world reality, that can reach it